(untitled) (Journal of Hama University, 2026)
Iser is considered the most important theorist of reception theory, as he is the guide of the theory. Iser was greatly influenced by different intellectual and linguistic theories. His work did not come out of nowhere, but rather benefited greatly from the theory of language action, psychology, logic, narrative theory, and communication theory. The research is an attempt to reveal the dimensions of reception theory as presented by Wolfgang Iser, as the cognitive frameworks of reception theory were drawn by Jauss and Iser. While Jauss focused on the collective and historical receptions of literary works, we find that Iser developed the concept of the reader. In this sense, the research hypothesis is determined by shedding light on Iser’s contributions to the development of the theory. The research relies on an approach that combines induction and interpretation, and its importance is determined by the fact that it procedurally separates reception theory as an individual project for Iser and reception as a theory that is the result of a collective effort, this effort that transferred the focus of critical interest From the text in structuralism to the reader after structuralism, the research was divided into four sections, which are: The first section: Reception. The second section: Wolfgang Iser. The third section: Reception between Iser and Jauss. The fourth section: Reception between Iser and Barthes. The fifth section: Reception between Iser and Derrida The research reached some results, perhaps the most prominent of which are: 1. Iser developed the concept of the reader, and established a strategy for reading, the features of which are determined by three elements, the first: the text, the second: how to approach the text through reading, and the third: the communication structure of literature. 2. Iser differed from Jauss in the linguistic treatment of reception theory, while Jauss was interested in literary history when receiving the text, Iser viewed the reading process as being based on two types of conflict. 3. Roland Barthes’s proposals constituted an actual addition to reception theory, as he defined the features of the reader and the conditions that must be met for reading, which made his views meet with Iser. 4. Derrida meets with Iser in elevating the status of the reader, and aims to liberate meaning from the constraint of closed, single reading linked to a specific and final meaning.